2022
DOI: 10.1590/0001-3765202220210566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host age, sex and life stage on the prevalence and abundance of sucking lice on Weddell seal in the Antarctic Peninsula

Abstract: Through evolutionary time, seal lice have developed morphological, behavioral, and ecological adaptations to cope with the amphibious lifestyle of their hosts in a coevolutionary process. Consequently, the dynamics of lice populations are determined by seals behavior. We aim to study the effects of host sex, age class, year, and sampling location, on the prevalence and mean abundance of Antarctophthirus carlinii, on Weddell seals (WS) Leptonychotes wedelli. The study was conducted at two sites in the Antarctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
3
1
Order By: Relevance
“…Our main conclusion is that A. lobodontis, from crabeater seals, and A. carlinii, from Weddell seals have different reproductive strategies. Although we did not have information on the reproductive season of crabeater seals, our results con rm that A. lobodontis would reproduce at least during the molting season of the seals, whereas the reproduction of A. carlinii would occur mainly during the reproductive season of seals (Soto et al 2022). As we will discuss, these differences may be related to their host's habitat use and foraging behavior.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…Our main conclusion is that A. lobodontis, from crabeater seals, and A. carlinii, from Weddell seals have different reproductive strategies. Although we did not have information on the reproductive season of crabeater seals, our results con rm that A. lobodontis would reproduce at least during the molting season of the seals, whereas the reproduction of A. carlinii would occur mainly during the reproductive season of seals (Soto et al 2022). As we will discuss, these differences may be related to their host's habitat use and foraging behavior.…”
Section: Discussioncontrasting
confidence: 48%
“…However, as WS dives deeper and longer than CS (91 m for 11.5 min; (Costa et al 2010)), lice would have less time to reproduce or at least to successfully hatch eggs. As we described in a previous study (Soto et al 2022), the main way of transmission of A. carlinii should be from female seals to their pups. We also observed that adult A. carlinii were more likely to be transmitted than nymphs and females more likely than males, the same pattern described for A. microchir from sea lions [6].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations